Islamic Educational Philosophy in the Context of Modern Education - M Zainul Mukhtar; Rosidin Rosidin; Siti Mutholingah (Civiliza Publishing, Indonesia., 2026)
Modern education faces a series of complex challenges. Rapid social change, the penetration of digital technology, an instant culture, and a moral crisis among the younger generation demand a more robust educational paradigm rooted in values. This paper aims to analyze the relevance of Islamic educational philosophy in the context of modern education. The discussion focuses on the nature of Islamic educational philosophy, the ontological, epistemological, and axiological dimensions of Islamic education, and its implications for educational design in the digital age. This research method utilizes a literature review, reviewing relevant books and scholarly articles, including one article specifically discussing Islamic educational philosophy and its scope. The analysis shows that Islamic educational philosophy can serve as an alternative paradigm to modern education, which tends toward secularism and technocracy. Education built on a framework of monotheism, the integration of knowledge and values, and an orientation toward morality provides a strong foundation for developing a more humane and sustainable curriculum, methods, and educational culture.